PEMBUATAN TONG SAMPAH SEBAGAI UPAYA PENINGKATAN KESADARAN LINGKUNGAN DAN KESEHATAN MASYARAKAT DI DESA PANDEAN - Anis, Nusron; Arum, Dwi Puspita Sari (COMVICE: Journal Of Community Service, 2025)
This Community Service Program (PKM) was conducted in Pandean Village, Rembang District, Pasuruan Regency, aiming to raise public awareness of environmental cleanliness and health through the creation of ergonomic waste bins made from recycled materials. The main issues identified were the lack of waste management facilities and low community awareness of waste sorting and household waste processing. The program applied the Participatory Action Research method, involving residents in all stages from planning to evaluation. The results showed increased community participation in maintaining cleanliness, the production of 15 functional waste bins, and the establishment of the environmental working group “Pandean Bersih.” Additionally, waste-based entrepreneurship training encouraged the emergence of creative economic initiatives among residents. This program demonstrates a sustainable and economically oriented model of community-based environmental empowerment.